Cenas de enunciação da propaganda de governo do estado do Pará: a constituição do mundo ético do sujeito político - BEZERRA, Diego Michel Nascimento (Universidade Federal do Pará, 2017)
Governmental propaganda texts are daily dispersed in the society through different media supports. This communicative activity projects an enunciative instance conditioned by senses from political and mediatic order. It is a discursive practice that aims to deliberately incorporate a public to a specific vision of the State, introducing an ethical world historically defined to legitimate the governmental image inserted in a democratic order. In this context, this research aims to understand what senses are implied in the enunciation of the propaganda of the government of Pará State, according to the semantics constrains imposed by the alignment between a political enunciative scene and an enunciative scene of propaganda. In order to demonstrate the way how the senses are processed in this discursive surface, it constituted a topic discursive unit of analysis with 52 pieces of propaganda in digital movie format that circulated for four years during the administration of a center-left party of the government of Pará State. Data was analyzed following the theoretical notions of global semantics (MAINGUENEAU, 2008a) that regulates the operation of discourse. It consolidated with the analysis of the results the following insights: (i) it established a global scene (MAINGUENEAU, 2008b, 2013, 2015) that projects the actional contexts between subjects from interdiscursive competencies implied in the production of symbolic materiality in matter, constituting a practice of hybrid communication that questions the coenunciator as citizen-spectator; (ii) it mobilized scenographies (MAINGUENEAU, 1997, 2008b, 2013, 2015) that impose effects of senses, which articulate to a deixis of a state prosperity to guarantee the enunciative authority of points of view held by social democracy supporters; (iii) it observed people who support a discursive ethos characterized by textual evidence that oscillate between a serious tone of impartiality and an emotional character of citizen gratitude, establishing order of the ideal of sociability among government and governed aiming the incorporation of the latter into the world of the senses of the government of Pará State.